An empirical study of food blogger influence on coffee shop brand image and consumer purchase decision in delapan gram - Suci Sandi Wachyuni; Kadek Wiweka; Indri Softia (Journal of Business on Hospitality and Tourism, 2021)
In recent years, food blogging has become a popular medium for sharing thoughts, feelings, opinions, and ideas. However, its impact on the beverage industry has not been widely studied. This study aims to examine the effect of food blogger promotion on brand image and purchasing decisions partially. This study took samples at the Delapan Gram Coffee Shop. The research method used in this research is the quantitative method. While the independent research variable is food blogger promotion (X), and the dependent variable is the brand image (Y1) and purchase decision (Y2). The data analysis method used in this study is multiple linear regression analysis using the SPSS program. This study found that food blogger promotion partially influences the brand image and purchasing decisions. However, brand image has a higher contribution to purchasing decisions than food blogger promotion. The practical implication of this research is as a reference for entrepreneurs, especially coffee shops, regarding the role of food bloggers in increasing sales. Meanwhile, the limitation in this study is that the sample scope is limited to one company. This study expects further research related to other factors that may have a greater influence on purchasing decisions.